On the Significance of Assumptions about Divine Goodness and Divine Ontology for ‘Logical’ Arguments from Evil - Bishop, John Christopher 1949- (2021)
Sterba’s Is a Good God Logically Possible? (2019) draws attention to the importance of ethical assumptions in ‘logical’ arguments from evil (LAfEs) to the effect that the existence of (certain types) of evil is incompatible with the existence of a God who is all-powerful and morally perfect. I argue, first, that such arguments are likely to succeed only when ‘normatively relativized’—that is, when based on assumptions about divine goodness that may be subject to deep disagreement. I then argue that these arguments for atheism are also, and more fundamentally, conditioned by assumptions about the ontology of the divine. I criticise Sterba’s consideration of the implications for his own novel LAfE of the possibility that God is not a moral agent, arguing that Sterba fails to recognize the radical nature of this claim. I argue that, if we accept the ‘classical theist’ account that Brian Davies provides (interpreting Aquinas), then God does not count as ‘an’ agent at all, and the usual contemporary formulation of ‘the problem of evil’ falls away. I conclude by noting that the question of the logical compatibility of evil’s existence with divine goodness is settled in the affirmative by classical theism by appeal to its doctrine that evil is always the privation in something that exists of the good that ought to be.
Keywords: God’s goodness; Classical Theism; Concepts of God; evil as privation of the good; existence of God; problem of evil